The renaissance of bridged triarylphosphines: Towards organophosphorus molecular bowls - Schaub, Tobias A.; Padberg, Kevin; Kivala, Milan (Chemistry Letters, 2019)
Bridged triarylphosphines represent conceptually simple members of an emerging class of polycyclic aromatic hydrocarbons with embedded phosphorus atoms. Their auspicious attributes have spurred a renewed scientific interest in these fascinating molecular bowls after having fallen into oblivion for more than two decades. In this Highlight Review historical aspects of fully bridged triarylphosphines are discussed and recent advances in this research field are summarized with a focus on the challenges that lie ahead.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Organophosphorus materials; Phosphorus heterocycles; Polycyclic aromatic hydrocarbons